2022
DOI: 10.1002/anie.202211601
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Organic Frameworks with Tailored Functionalities for Modulating Surface Potentials in Triboelectric Nanogenerators

Abstract: Designing materials with high triboelectric is an efficient way of improving output performance of triboelectric nanogenerators (TENGs). Herein, we synthesized a series of covalent organic frameworks (COFs) with similar skeletons but various functional groups ranging between electron-donating and electron-withdrawing. These COFs form an ideal platform for clarifying the contribution of each group to TENG performance because the pore wall is perturbed in a predesigned manner. Kelvin probe force microscopy and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The actuator generates mechanical motions by means of environment stimuli, showing spontaneity to trigger the triboelectric effect. PVP/PAA nanofibers-network loaded MIL-88A delivers high surface roughness and electron trapping ability, which could effectively improve the triboelectric performance. ,, To achieve the T-HRA with self-powered perception capability, we systematically evaluated the triboelectric performance of T-PPMs with different contents of MIL-88A, at the relatively low ambient humidity of RH = 35–40%, to largely avoid the interference of humidity on the triboelectric output. The T-PPM-based single electrode TENG has the same device structure with T-HRA; herein, the T-PPM acts as the triboelectric active layer and the conductive fabric serves as the electrode for collecting electricity (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…The actuator generates mechanical motions by means of environment stimuli, showing spontaneity to trigger the triboelectric effect. PVP/PAA nanofibers-network loaded MIL-88A delivers high surface roughness and electron trapping ability, which could effectively improve the triboelectric performance. ,, To achieve the T-HRA with self-powered perception capability, we systematically evaluated the triboelectric performance of T-PPMs with different contents of MIL-88A, at the relatively low ambient humidity of RH = 35–40%, to largely avoid the interference of humidity on the triboelectric output. The T-PPM-based single electrode TENG has the same device structure with T-HRA; herein, the T-PPM acts as the triboelectric active layer and the conductive fabric serves as the electrode for collecting electricity (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…6d), and then composited as fillers in PVDF as a tribo-layer. 137 With the strong electron-withdrawing ability of 4F-groups, 4F-COF has increased charge-trapping sites and electron affinity (Fig. 6e), and consequently has the most negative property and maximum power density (2858 mW m À2 ) compared with other COFs.…”
Section: Covalent Organic Framework (Cofs) As Triboelectric Polymersmentioning
confidence: 99%
“…[51] In this regard, as previously reported that modification of polymer films with different functional groups can significantly modulate their triboelectric properties to achieve enhanced performance TENGs. [52][53][54][55] Thus, COFs with such tunable properties show great potential in fabricating high-performance TENGs to further promote their widespread application and may also deepen our understanding of the essential mechanism of triboelectrification.…”
Section: Introductionmentioning
confidence: 99%